Germany 1923 hyperinflation, Hitler's putsch, and democracy in crisis - Ullrich, Volker 1943- (Liveright Publishing Corporation, 2023)
"As the great Austrian writer Stefan Zweig confided in his autobiography, written in exile, 'I have a pretty thorough knowledge of history, but never, to my recollection, has it produced such madness in such gigantic proportions.' He was referring to the situation in Germany in 1923. It was a 'year of lunacy,' defined by hyperinflation, a political system on the verge of collapse, and separatist movements that threatened Germany's territorial integrity. Most significantly, Adolf Hitler launched his infamous Beer Hall Putsch in Munich--a failed coup that nonetheless drew international attention and demonstrated the Nazis' ruthless determination to seize power. In Germany 1923, award-winning historian Volker Ullrich draws on letters, memoirs, newspaper articles, and other sources from the time to present a captivating new history of those explosive twelve months.
"Originally published in German as Deutschland 1923"--Title page verso
Keywords: Geschichte 1923; Deutschland; Germany / History / 1918-1933; Germany / Politics and government / 1918-1933; Germany / Economic conditions / 1918-1945; Allemagne / Histoire / 1918-1933; Allemagne / Politique et gouvernement / 1918-1933; Allemagne / Conditions économiques / 1918-1945; HISTORY / Europe / Germany; Economic history; Politics and government; Germany; 1918-1945; History; Informational works